RSMC Method: Cultivating Characters in Early Childhood - Massika, Shofi; Syafril, Syafrimen; Jatmiko, Agus; Setiana, Nurul; Yaumas, Nova Erlina (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
In the school-based education system, educators often prioritize cognitive development over students' emotional development. It is crucial to instill good character in children from a young age as it influences them well into adulthood. Research indicates that the RSMC method is effective for nurturing early childhood character traits. This study examines the application of the RSMC method in Kindergarten, using a single case design with a holistic approach. Data collection methods included observation, interviews with an experienced educator, and documentation of lesson plans and curriculum structures. The Milles and Hubermen interactive model was employed for data analysis, involving descriptive data collection, data reduction, and data presentation to draw conclusions. The findings suggest that the RSMC approach, comprising Scheduled Routine Activities (R), Unscheduled Spontaneous Activities (S), Modelling and Giving Examples (M), and Environmental Conditioning (C), effectively fosters character development in daily activities. This method can assess changes in students' behavior resulting from specific stimuli and responses. Therefore, the RSMC method developed in this study offers a viable option for early childhood character cultivation. Further research should explore the long-term effectiveness of different positive bias methods for character education in early childhood.